Anthropometric values, education and occupational situation of parents and the occurrence of overweight and obesity among junior high school students - Machniak, Mariusz; Podhorecka, Marta; Zukow, Walery; Chwałczyńska, Agnieszka (Journal of Education, Health and Sport, 2019)
Introduction: Overweight and obesity is ever more affecting the youngest children. According to the International Obesity Task Force report, an increase of over 400,000 overweight children is being noted each year. The reason of such exacerbation varies in nature and is strongly corelated with parents’ behavior towards their dependents’ dietary requirements together with the neglect of encouragement towards physical activity. Material and Methods: TANITA body composition analyzer has been used to study 200 teenagers in the age of 14 to 16 years old, pupils of one of the secondary schools in the Lower Silesian in Poland. The questionnaire was directed to parents and adolescents regarding physical activity, social and economic status and parents' anthropometric data. The adolescents were additionally subjected to height and body weight measurements.Results: The results of the study show direct correlation of the higher education of parents (mainly mothers) on the increase of undertaking extracurricular physical activities by overweight or obese girls.Conclusions: It has been concluded that there is a relationship between the BMI of the examined girls and the BMI of the father. Also, the study proves paramount impact of mother's education and father's professional status on the physical activity of the examined youth.